The systematic study of the Japanese Protoflorideae - Tanaka, Takesi (Kagoshima, Japan The Faculty of Fisheries, Kagoshima University, 1952)
Memoirs of the Faculty of Fisheries Kagoshima University vol.2 (2)
Keywords: Protoflorideae